Mini-cutting rooting and plantlet growth in Erythrina crista-galli L. - Bisognin, Dilson Antônio; de Araujo Lopes, Gabriel; Costa Malheiros, Angélica; Trevisan, Renato; Haygert Lencina, Kelen (Revista Ceres, 2025)
In this study, we evaluated the adventitious rooting competence of mini-cuttings and plantlet growth of two clones of swamp cork (Erythrina crista-galli L.). Experiments were carried out in a factorial of two clones to study the need of application of indolebutyric acid (IBA), substrate composition for mini-cutting rooting and plantlet growth, and rooting curves of the clones 15SM05 and 15SM08, in the completely randomized design. Mini-cuttings of swamp cork clones showed high rooting competence, with mean rooting percentage above 80% even without IBA application. Vermiculite and its combination with commercial substrate resulted in the highest percentage of rooting, and number and length of roots and shoots. The clones showed differences regarding their adventitious rooting competence and the increment in rooted mini-cuttings with time in a humidity chamber, being the clone 15SM05 the most suitable for plantlet production.